(untitled) (Modern education and development, 2025)
In the modern world, people are increasingly seeking environments that promote relaxation, mindfulness, and well-being. Interior design plays a crucial role in shaping these experiences, and one of the most effective ways to create calming spaces is by integrating natural elements. Natural materials, greenery, and elements such as light and water can have a profound impact on the emotional and psychological state of individuals. This article explores the role of natural elements in interior design, examining their benefits and how they contribute to creating serene, restorative environments in both residential and commercial spaces.